State studies of the large-scale electric fields in the low-latitude region of Earth's inner magnetosphere - Zhao Zhang; Dianjun Zhang; Wenlong Liu (地球与行星物理论评)
The large-scale electric fields in Earth's inner magnetosphere are generated by the interaction between the solar wind and Earth's magnetic field. In high-latitude regions, parallel electric fields are dominant, while in low-latitude regions, the convection, corotation, and impulsive electric fields play a crucial role in the dynamics of the inner magnetosphere. This review examines the characteristics of large-scale electric fields in low-latitude regions and their effects on magnetospheric processes. The convection and corotation electric field, driving the plasma drift, determine the topology of the plasmasphere. The impulsive electric field, accelerating charged particles quickly, leads to the inward injection of energetic particles. Convection electric fields, driven by dayside plasma flows from the magnetotail, exhibit a non-uniform spatial distribution. Recent satellite observations reveal that their distribution is influenced by geomagnetic and solar activity. Shielding effects limit the dawn-to-dusk electric field within approximately 5 Earth radii (RE) during low geomagnetic activity (e.g., Kp=1), with the shielding boundary shifting inward as geomagnetic activity intensifies. Subauroral polarization streams are associated with intense radial electric fields at approximately 4 RE, significantly affecting the distribution of the convection electric field from dusk to midnight. Recent studies also show that the convection electric field distribution varies during different phases of magnetic storms, with electric fields penetrating deeper into the inner magnetosphere during the main phase, and shielding effects dominating during the recovery phase. During the magnetic storm's main phase, or after a southward turning of the interplanetary magnetic field, the dawn-to-dusk electric field is enhanced, with the amplitude and response time varying across different regions. Corotation electric fields arise from the plasma's rotational motion with Earth. However, observations indicate that the plasmasphere experiences a corotation lag, suggesting that corotation electric fields may be overestimated when based on the 24-hour corotation period of the plasmasphere. Recent studies have shown that this corotation lag may be linked to energy and momentum transfer processes in the ionosphere or thermosphere. The ionospheric dynamo mechanism, driving neutral winds toward the equator, plays a critical role in this corotation lag. Impulsive electric fields are transient phenomena triggered by interplanetary shocks or substorms. They play a crucial role in accelerating charged particles, leading to inward injections of energetic particles. SWMF simulations have provided insights into the spatiotemporal evolution of impulsive electric fields during interplanetary shock events. The propagation speed of impulsive electric fields is closely related to the propagation speeds of fast-mode waves and interplanetary shocks, which determine their initial response and peak arrival times. Despite significant advancements, challenges persist in accurately modeling shielding and penetration electric fields, understanding their global and synchronous response to interplanetary magnetic field variations, and distinguishing between different types of electric fields. Addressing these challenges is essential for advancing our understanding of the magnetosphere's dynamics and its interaction with the solar wind. This review summarizes recent advances in the study of convection, corotation, and impulsive electric fields, highlighting unresolved scientific questions and the need for further investigations in the inner magnetosphere.